2017
DOI: 10.1111/jcpe.12655
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological changes after ridge preservation with two xenografts: preliminary results from a multicentre randomized controlled clinical trial

Abstract: The ridge preservation procedures had significantly better outcomes when compared to natural healing. The biomaterials did not differ for maintenance of bone width; even though, the bone height seemed to be better preserved with the cortical porcine bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
3
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(103 citation statements)
references
References 30 publications
3
91
3
5
Order By: Relevance
“…Results showed that the use of collagen membrane alone or associated to porcine-derived bone improves the healing bone process, compared to that of extraction sites spontaneously healed. These outcomes are in agreement with data reported by other studies [17,18], and confirm that porcine-derived bone and reabsorbable membrane are effective in maintaining the post-extractive ridge volume, compared to spontaneously healed extraction sites. As previously reported [16] the comparative clinical results between the three experimental groups, showed that at 4 months re-entry surgery, extraction sockets without severe walls deficiencies and with vestibular bone thickness ≥ 1.5 mm, grafted with porcine-derived bone and/or covered by collagen membrane have significantly lower vertical and horizontal bone changes compared to extraction sockets left to heal spontaneously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results showed that the use of collagen membrane alone or associated to porcine-derived bone improves the healing bone process, compared to that of extraction sites spontaneously healed. These outcomes are in agreement with data reported by other studies [17,18], and confirm that porcine-derived bone and reabsorbable membrane are effective in maintaining the post-extractive ridge volume, compared to spontaneously healed extraction sites. As previously reported [16] the comparative clinical results between the three experimental groups, showed that at 4 months re-entry surgery, extraction sockets without severe walls deficiencies and with vestibular bone thickness ≥ 1.5 mm, grafted with porcine-derived bone and/or covered by collagen membrane have significantly lower vertical and horizontal bone changes compared to extraction sockets left to heal spontaneously.…”
Section: Discussionsupporting
confidence: 92%
“…Contradictory considerations are reported in literature on the “biological meaning” of residual graft particles present in biopsy samples harvested from regenerated extraction sockets. Highlighting that the almost complete incorporation of the residual graft particles in bone creates a dense and hard tissue network with particles completely surrounded by vital bone, some authors [17,18] suggested that, once the biomaterial particles are embedded in mineralized bone, they acted similarly to the host bone, providing a similar biologic support. On the contrary, other authors [31,32] having identified the presence of multinucleated cells and of osteoclastic activity around xenogenic bone residual particles suggested that these may influence the remodelling process and delay the socket healing.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of primary outcomes revealed no significant histological differences in mean vital bone formation between ridge preservation with cancellous bovine xenograft and cancellous porcine xenograft after 18 to 20 weeks of healing. For the porcine group, vital bone formation of 31.3% in the current study was similar to previously reported results for ridge preservation using cortical and collagenated cortico‐cancellous porcine xenograft showing vital bone formation of 36.8% and 41.4%, respectively, after 3 months of healing . Conversely, the ridge preservation study of Guarnieri et al .…”
Section: Discussionsupporting
confidence: 91%
“…To minimize this physiologic process, several therapeutic attempts have been investigated, a concept defined as “alveolar ridge preservation” (ARP) . Over the past 2 decades, studies have used different techniques and materials, all aimed at reducing the post‐extraction alveolar ridge atrophy . Among many different materials that have been used throughout the literature, the autogenous bone has been regarded as the gold standard for replacing or regenerating the resorbed alveolar ridge due to the fact that it consists of all necessary properties required in bone regeneration (osteoconduction, osteoinduction, and osteogenesis) .…”
Section: Introductionmentioning
confidence: 99%